GNSS Radio Occultation: a Review of the Theory, Missions, and Products - Jerez, Gabriel Oliveira [UNESP]; Alves, Daniele Barroca Marra [UNESP]; Nespolo, Raphael Silva [UNESP]; Monico, João Francisco Galera [UNESP]; Hernández-Pajares, Manuel (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2022)
Radio occultation (RO) have been used for probing the atmosphere of other planets since the 1960s. With the development of Global Navigation Satellite System (GNSS) and missions with Low Earth Orbit (LEO) satellites emerged the possibility of investigations of the Earth's atmosphere with the application of RO-GNSS. From the GNSS satellites to the receivers onboard LEO satellites, the propagated signals are influenced by the atmosphere in different ways. The transmitted signal is refracted, so it can be collected by the onboard receiver in spite of the superposition made by the Earth. This geometry makes it possible to calculate refractive indices, which contain information about the composition of the Earth's atmosphere. Several profiles can be obtained from the refractive index, for instance temperature, pressure, and electron density. In this paper a theoretical review of the GNSS-RO technique is carried out, aiming to present the technique and its potential to researchers from various areas who have the possibility of using it. First, a brief history of the development of the technique is presented, as well as the main missions related to this topic, including the status of missions currently operational and some future perspectives. In addition, the main elements involved in the occultation geometry are presented, as well as the main concepts and formulations for obtaining the profiles. Finally, some products from RO-GNSS missions are presented and analyzed.
Rádio Ocultação GNSS: Revisão Teórica, Missões e Produtos
Keywords: Atmosphere; Atmospheric profiles; GNSS; Radio occultation